Avaliação agronômica, estabilidade e adaptabilidade de genótipos de feijoeiro comum - Borges, Márcio Hedilberto Cunha (2005)
The objective of this research was to evaluate common beans cultivars as well as elite improved strains, aiming at their recommendation for cultivation in the State of Minas Gerais as well as to verify and analyze adaptability and stability of the genotypes involved. Plant morphological characteristics which influence directly the harvest process, as well as production factors and resistance to bacterium blight were also evaluated. Five experiments were conducted in the following environments: winter season of 2003, raining season (2003/2004) in both Uberlândia and Formoso, dry season (2004) in Uberlândia, Minas Gerais. The genotypes under study were twenty four entries of commom beans encompassing cultivars and advanced strains of the followings groups: carioca (BRS Horizonte, Perola, Iapar 81, BRS Requinte, CNFC 7726, BRS Pontal), jalo, (Goianao Precoce, Jalo EEF 559, Jalo Precoce), preto (BRS Grafite, BRS Valente, CNFR 7726, BRS Campeiro, BRS Supremo, Uirapuru), rajado (BRS Radiante, Irai, Diacol Calima), roxo (Roxo 90, CNFR 7847, BRS Timbó, BRS Pitanga, Vermelho 2157) and rosinha (BRS Vereda). It was adopted the randomized complete-block design with 3 replications and the plots comprised four rows 4 meters long with a row spacing of 0,5 meters between them. In the carioca group, the cultivar BRS Pontal presented the highest yield and adaptability, and the cultivar BRS Horizonte showed superior traits related to harvest; in the jalo group the cultivar jalo was outstand for its stability and superior yield compared to the checks in general and specially under unfavorable environment. In the black group the cultivars BRS Campeiro, Brs Supremo and IPR Uirapuru, presented the best results for yield and yield stability. The cultivar BRS Supremo showed a better architecture and a higher level of resistance to lodging compared to the genotypes of the roxo and rosinha groups. The red cultivar 2157, followed by the cultivars BRS requinte and BRS Pitanga, were outstand for their yields, adaptabilities and yield stabilities and also for grain quality. There was a positive significant correlation between yield and number of pods per plant, number of grains per pod as well as cultivar cycle.